PTU-093 An Exploration of Adverse Reactions to Foods in Adults with Crohn's Disease. (17th August 2016) - Morris, A; Leach, B
Abstract : Introduction: Crohn's Disease (CD) has been associated with an increased risk of food allergies due to damage to the epithelial intercellular junctions and the ensuing immune response. However, since this population has increased micronutrient requirements it is important that dietetic advice is sought in favour of self-imposed dietary restrictions. The aim of this study was to explore individuals with CD's experiences of self-reported adverse reactions to food. Methods: A phenomenological design utilised in-depth semi-structured interviews with adults with CD. Convenience sample recruitment via Coventry Ileostomy and Internal Pouch Support Group was employed. A topic guide included the areas of experinces of adverse reactions to foods, ways of coping and impact of adverse reactions to foods. Interviews were recorded and transcribed verbatim. Data was explored and findings interpreted using Interpretive Phenomenological Analysis. NVIVO software was used for data management. Member checking and internal peer review were undertaken. Participants gave written informed consent. Results: Ten adults (4 men 6 women) with a mean age of 52.2 (±19) years had a mean experience of 20.2 years living with CD. Four main themes emerged which illustrated the experience of adverse reactions to food (1) Physiological symptoms; pain; swelling; diarrhoea; breathing difficulty (2) Difficulties Identifying and telling the difference between allergy and intolerance; being able to identify an allergic reaction, Hypersensitivity to food items dependent on situation rose, e.g. inside/outside home (3) Psychological reaction to food, questioning their own working diagnosis and reactions to certain foods (4) Dietary self-management; excluding offending foods from diet; taking antihistamine medication; not re-engaging with dietitians due to perceived lack of adverse food reaction knowledge in CD. Conclusion: Adults with CD reported common adverse reactions to certain foods. Coping strategies included identifying the symptoms and ascribing them either to an allergic reaction or intolerance, with subsequent exclusion of offending foods or decisions on excluding foods likely to cause intolerance. Health professionals may need to be aware and more supportive around reports of adverse reactions to foods and the potential impact on quality of life in CD. Building working relationships is required to support the patient and ensure the nutritional consequences of food avoidance are minimised. Disclosure of Interest: None Declared